Peran BP4 Kota Pekalongan dalam Upaya Pembangunan Ketahanan Keluarga di Kota Pekalongan - Kurniati, Atik (Al-Hukkam: Journal of Islamic Family Law, 2021)
BP4 in Pekalongan City has contributed to the development and preservation of families, where the work of BP4 is supported by the city government and synergizes with other agencies in order to realize the government program m, namely family resilience. The formulation of the research problem how is the role of BP4 Pekalongan City in efforts to build family resilience? what factors hinder and support BP4 Pekalongan City's efforts in building family resilience? This type of research uses field research with qualitative approach. The results of this study indicate that the role of BP4 Pekalongan City is to participate in efforts to realize the development of family resilience, namely by socializing the Pekalongan City Regulation Number 8 of 2019 concerning Family Resilience Development, implementing Suspranik, Suscatin and fostering sakinah families through formal education forums and taklim assemblies in partnership with BP4 Pekalongan City. The factors that support the development of family resilience carried out by BP4 Pekalongan City are divided into two, namely internal factors and external factors. While the inhibiting factors include the economy of the people of Pekalongan City which is still minimal and some Catin who do not follow Suspranik and Suscatin at BP4 Pekalongan City.